Growth, poverty and developmental aspects of agriculture : countries' perspectives - Das, Ramesh Chandra (Emerald Publishing Limited, 2024)
Agricultural growth, bolstered by technological advancements and international trade, enhances economic stability and food security in many developing nations in one hand, and reduces income disparities between developed and less developed nations on the other. However, the instability in agricultural output, yield rates and prices underscore the need to stabilize agro-variables for sustained food security in the long term. In Growth, Poverty and Developmental Aspects of Agriculture: Countries' Perspectives, authors delve into diverse aspects of agricultural economics and food security across various regions. Authors cover topics such as the efficiency of foodgrain production, the impact of bank financing on agricultural growth, foreign direct investment in agriculture, agricultural exports, crop insurance practices and the volatility of crop prices. Additionally, the study examines national security concerns related to food insecurity, environmental health implications, regional disparities in food security and policy analysis in various countries including India, Pakistan and Afghanistan. With contributions from scholars around the world, the book offers a comprehensive exploration of the complexities surrounding agricultural economics and food security. This collected edition is essential for scholars and professionals in agricultural economics, food security, international trade and development studies. Professionals in government agencies, NGOs and international organizations involved in policymaking and agricultural development may also benefit from diverse perspectives on food security initiatives.